Circulating Levels of Brain‐Derived Neurotrophic Factor and History of Suicide Attempts in Women. Issue 1 (28th September 2017) - Kudinova, Anastacia Y.; Deak, Terrence; Deak, Molly M.; Gibb, Brandon E.
Abstract : A growing body of research examining biological factors associated with suicidal behaviors highlights the role of brain‐derived neurotropic factor (BDNF), involved in neurogenesis and synaptic plasticity. There is evidence suggesting that suicide attempters have lower BDNF levels than those with no history of suicide attempts. The key question addressed in the current investigation is whether differences in circulating BDNF levels persist beyond the current suicidal episode and would be observed in those with a past history of suicide attempts (SA). Plasma levels of BDNF were assessed in 73 women from the community. We found that women with a history of SA exhibited lower levels of BDNF than women with no SA history and this difference was maintained after statistically controlling for the influence of other potential psychiatric or demographic factors. These findings support and extend existing research by suggesting that circulating BDNF levels are decreased among individuals with a history of SA compared to individuals with no history of SA. This relation appeared to be specific to women's history of SA and was not explained by other potential psychiatric or demographic factors, which further highlights the role of BDNF as a promising biomarker for suicidal behavior.